Municipal-Indigenous Relations in Atlantic Canada - Heritz, Joanne (The International Indigenous Policy Journal, 2024)
The significant increase in the urban Indigenous identity population in Atlantic Canada in the past ten years warrants an investigation of urban Indigenous policies that asks, to what extent are municipalities in Atlantic Canada bridging relations with urban Indigenous Peoples? Over half of Canada’s Indigenous Peoples reside in urban centres, yet no one level of government has taken responsibility for developing policies regarding urban Indigenous Peoples. Since the new millennium, municipalities are bridging relations with urban Indigenous Peoples. Not only are these initiatives in Western and Central Canadian municipalities varied, but they are also understudied. An analysis of Municipal-Indigenous relations in Charlottetown, Fredericton, Halifax, and St John’s addresses the following: municipal capacity for Indigenous inclusion; urban Indigenous policy initiatives; and the extent to which municipalities are responding to the Calls to Action by the Truth and Reconciliation Commission.